ISU-ISU BERKAITAN EKONOMI GIG DI JEPUN: ANALISIS LAPORAN AKHBAR - Omar, Siti Aminah; Paidi, Rohayati; Furuoka, Fumitaka (WILAYAH: The International Journal of East Asian Studies, 2023)
The global COVID-19 pandemic has transformed the media landscape in Japan, as news coverage that previously focused on the preparation for the Tokyo 2020 Olympics has shifted towards pandemic-related issues. Increased news reports on current pandemic-related issues, including those related to gig economy workers, have emerged. Social restrictions and the rise in online activities have driven the growth of the gig economy in Japan, which was initially needed to address the imbalance in talent supply and demand, along with a declining young population. However, a lack of legal oversight has led to various issues, ultimately resulting in the formation of labor unions demanding job justice for gig workers. Previous studies have been conducted on gig workers, such as labor injustices and proposals for regulating labor standards like collective bargaining, but there is still a lack of research exploring media reporting on the gig economy in Japan. Therefore, this study aims to identify current issues related to the gig economy in Japan, focusing on online food delivery platform workers through media coverage analysis. Data was collected from the online news archive of Asahi Shimbun from February 2021 to December 2022 using the search terms "gig economy" and "uber eats." The research findings were obtained through content analysis conducted with the assistance of Leximancer software. It was found that Asahi Shimbun’s news reporting on the gig economy during the COVID-19 pandemic tended to be more negative in sentiment than positive. Negative sentiment emerged due to prominent reports of dissatisfaction among gig workers with the Uber Eats Japan food delivery service company, primarily stemming from changes in the delivery compensation system. This study is expected to contribute to the understanding of gig economy issues as portrayed in the media, serving as a guide for policymakers, industry stakeholders, and labor unions to improve the quality of gig work in Japan and globally.